A Pilot Study Examining Speed of Processing Training (SPT) to Improve Processing Speed in Persons With Multiple Sclerosis - Nancy D. Chiaravalloti; Nancy D. Chiaravalloti; Yael Goverover; Yael Goverover; Silvana L. Costa; Silvana L. Costa; John DeLuca; John DeLuca; John DeLuca (Frontiers in Neurology, 2018)
Background: Individuals with Multiple Sclerosis (MS) have significant impairments in processing speed (PS) and such impairments may underlie other cognitive deficits common in MS and limit performance of everyday life activities.Objective: To examine the efficacy of a computerized PS intervention, Speed of Processing Training (SPT), in persons with MS on PS, memory and everyday activities.Methods: Twenty-one individuals with clinically definite MS and an objectively assessed impairment in PS were included in a controlled randomized clinical trial, randomly assigned to a treatment group or a control group. Participants were assessed prior to and within 1 week of completing the treatment. Outcome measures included traditional neuropsychological tests measuring PS and memory, and an assessment of PS in daily life activities.Results: The treatment group showed a significant improvement on neuropsychological tests of PS and new learning and memory. A significant improvement was additionally noted in the treatment group on measures of PS in everyday life. These changes were not observed in the control group.Conclusions: Results provide preliminary data in support of SPT in treating PS deficits in persons with MS. Additional research is needed with larger samples and more comprehensive outcome measures.